2015
DOI: 10.1128/aem.00027-15
|View full text |Cite
|
Sign up to set email alerts
|

Solar and Temperature Treatments Affect the Ability of Human Rotavirus Wa To Bind to Host Cells and Synthesize Viral RNA

Abstract: Rotavirus, the leading cause of diarrheal diseases in children under the age of five, is often resistant to conventional wastewater treatment and thus can remain infectious once released into the aquatic environment. Solar and heat treatments can inactivate rotavirus, but it is unknown how these treatments inactivate the virus on a molecular level. To answer this question, our approach was to correlate rotavirus inactivation with the inhibition of portions of the virus life cycle as a means to identify the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…RVA was detected throughout the year and followed a seasonal distribution, similar to previous reports in which peaks were observed in the winter months [29][30][31] 5 years of age were correlated with temperature (r = À0.68, P = 0.01) [32], and our study also found a negative correlation between RVA-positive rate and temperature. As the total positive rate of acute gastroenteritis viruses had no correlation with temperature, it could not be the bacteria-induced food poisoning in summers that raised the total number of included diarrhoea outpatients which resulted in lower RVA-positive rates in winters.…”
Section: Rva-negative Samplesupporting
confidence: 91%
See 1 more Smart Citation
“…RVA was detected throughout the year and followed a seasonal distribution, similar to previous reports in which peaks were observed in the winter months [29][30][31] 5 years of age were correlated with temperature (r = À0.68, P = 0.01) [32], and our study also found a negative correlation between RVA-positive rate and temperature. As the total positive rate of acute gastroenteritis viruses had no correlation with temperature, it could not be the bacteria-induced food poisoning in summers that raised the total number of included diarrhoea outpatients which resulted in lower RVA-positive rates in winters.…”
Section: Rva-negative Samplesupporting
confidence: 91%
“…However, in India and Republic of Congo, both vomiting and fever were significantly more commonly associated with RVA-positive cases [33,36], which may be because the study in India used ELISA to detect rotavirus and the study in Congo only included hospitalised children. We also found that outpatients in winter had significantly higher frequencies of fever and respiratory diseases than in summer, indicating RVA may be more virulent at low temperatures, which is partly consistent with the high temperature-caused loss of infectivity [32]. However, the relation between temperature and virulence has rarely been discussed and needs further study.…”
Section: Rva-negative Samplesupporting
confidence: 66%
“…Nuanualsuwan and Cliver (72) reported that the primary target of poliovirus, hepatitis A virus, and feline calicivirus inactivation at 72°C was the capsid, and that inactivation occurred by conformational change of the viral proteins. Similarly, Romero-Maraccini et al (73) proposed that rotavirus inactivation at 57°C was linked to a disruption of protein-mediated steps of the early life cycle. Finally, the virucidal mode of action of high temperature and pH may also involve a denaturation of the viral capsid proteins that allows for the release of the genome from the capsid.…”
Section: Discussionmentioning
confidence: 97%
“…6a(iii)) of rotavirus, which could explain about half of the inactivation that was observed; the remaining inactivation was attributed to post-translational steps. 99 As discussed in Section 4, nucleic acid and protein monomers are susceptible to direct endogenous reactions. It is therefore likely that these reactions play a role in virus inactivation.…”
mentioning
confidence: 99%